The rise of the urban South - Larsen, Lawrence H. (Lawrence Harold), 1931-2017 (The University Press of Kentucky, 2015)
Operating under an outmoded system of urban development and faced by the vicissitudes of the Civil War and Reconstruction, southerners in the nineteenth century built a network of cities that met the needs of their society. In this pioneering exploration of that intricate story, Lawrence H. Larsen shows that in the antebellum period, southern entrepreneurs built cities in layers to facilitate the movement of cotton. First came the colonial cities, followed by those of the piedmont, the New West, the Gulf Coast, and the interior. By the Civil War, cotton could move by a combination of road, rai.